Youth Perceptions of Shemale; Celebrated TV Idols and Inglorious Public Ignominy - Muhammad Fawwaz Farhan Farabi; Ahmad Farhan Malika (Westscience Press, 2023)
Shemale is a condition for a person who is medically male but behaves and acts like a woman. In general religious and socio-cultural views, the position of shemale is considered as part of a social deviation, which implies limited access to socio-economy, education, and other public spaces. The social marginalization of shemale, in turn, exacerbates the quality of life for shemale themselves. This condition is different from someone who identifies as shemale in the entertainment industry. In the world of entertainment, identity as shemale tends to get better reception and get a special space. This study uses a quantitative approach with descriptive-analytical methods on several data obtained from a data collection instrument in the form of a questionnaire and interview. The questionnaire was used to assess adolescents' views on the rise of celebrities who use shemale identity as a breaker in the world of entertainment as well as to assess the views of adolescents in accepting shemale groups in various social aspects, such as educational opportunities, work, and also family life which are calculated in numbers spread through an online form. The results of the data show that both in social and entertainment in general, adolescents tend not to reject the existence of a shemale, feel that their behavior is funny, and there are high doubts about whether this is appropriate.